1978
DOI: 10.1073/pnas.75.1.319
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dibutyryl cyclic AMP and microtubule organization in contracting heart muscle cells.

Abstract: Rhythmic and synchronous contractions of interconnecting myocyte cultures prepared from fetal rat hearts are arrested upon the addition of 0.2-2.0 mM N6,02'-dibutyryladenosine 3':5'-cyclic monophosphate (Bt2cAMP). The contractions arrested by Bt2cAMP are restored either by diluting the Bt2cAMP from the media or by adding colchicine. While colchicine restores Bt2cAMP-arrested myocyte contractions at concentrations as low as 1.0 jIM, the inactive isomer lumicolchicine shows no effect. Morphologically, Bt2cAMP tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Although many were oriented parallel to myofilaments, others intersected myofilament bundles at a variety of angles. Similar microtubule arrangements have been observed in the intact ventricle (Goldstein and Entman, 1979) and neonatal myocyte cultures (Nath et al, 1978).…”
Section: Myofilaments and Microtubulessupporting
confidence: 53%
“…Although many were oriented parallel to myofilaments, others intersected myofilament bundles at a variety of angles. Similar microtubule arrangements have been observed in the intact ventricle (Goldstein and Entman, 1979) and neonatal myocyte cultures (Nath et al, 1978).…”
Section: Myofilaments and Microtubulessupporting
confidence: 53%
“…Although we (5) and others (3,4) have reported that certain tubulin-binding agents stimulate the spontaneous frequency of individual cardiac cells, it was not clear whether this was a general property of all tubulin-binding agents. Our studies here demonstrate across a wide range of compounds that those tubulin-binding agents that depolymerize microtubules (i.e., vinca alkaloids, colchicine, nocodazol, and podophylotoxin) have very early or immediate effects on heart cell beating.…”
Section: Discussionmentioning
confidence: 99%
“…There have been, however, three scattered reports (3)(4)(5), one of which comes from the laboratory of T.J.L. (5), suggesting that tubulin-binding agents can affect the rate of spontaneously beating cardiac cells growing in vitro (3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Each enzyme phosphorylates MAP2 in vitro, decreasing the ability of MAP2 to promote microtubule assembly (Yamamoto et al, 1985). Since cAMP and Ca2" plus calmodulin effect the number and organization of microtubules in intact cells (Kram & Tomkins, 1973;Nath et al, 1978;Keith et al, 1983), it is possible that phosphorylation of MAPs may be one mechanism for modulating microtubule function.…”
Section: Introductionmentioning
confidence: 99%